Organizational Commitment Viewed from Manager’s Transformational Leadership Style - Tentama, Fatwa (Universitas Ahmad Dahlan, 2014)
ABSTRACTThe research aims at testing empirically the influence of manager’s transformational leadership style on organizational commitment. The proposed hypthesis is positive relationship between manager’s transformational leadership style and organizational commitment.The subjects of the research are 40 employees of Batik Company “Nyonya Indo”. The subjects used in the research should meet the requirements, i.e.: 1). Men and women, 2). Permanent employee, 3). Have been working at least for a year. Transformational leadership style and organizational commitment scales were used to collect the data. The method of data analysis used is product moment correlation of Pearson through SPSS program of 17.00 for windows version. The result shows that there is significant positive correlation between manager’s transformational leadership style and organizational commitment. This is depicted in r = 0,297 and p < 0,05. It means that the higher the transformational leadership style is applied, the higher the organizational commitment and vice versa. The number of the influence of manager’s transformational leadership style on organizational commitmentis 7,841 %.Keywords: organizational commitment, transformational leadership style,